A REVIEW OF VARIOUS HEAT EXCHANGER ABOARD AUTONOMOUS SHIP - Bintang Fikri; Barokah (Jurnal Maritim Malahayati, 2022)
Heat exchanger is one of the important device aboard the ship to reduce heat and prevent the overheating as overheating in the ship could damage the machinery used in the ship. There are parameters to be considered in the design, and operating the heat exchanger, especially in the autonomous ship. In this paper, a general review is provided of developments and improvements on heat exchanger and its relevance in an autonomous ship. Based on the finding, the design and heat exchanger typing should be adapted well to the applications in which they are used. As the usage in an autonomous ship, an risk and reliability assessment of heat exchanger have to be analyzed. Lastly, the development of heat transfer usage in an autonomous ship is still in the stage of monitoring and measuring the operating parameter. The maintenace and correction of the failures still need human presence.